Battlefield of the mind [electronic resource] : winning the battle in your mind - Meyer, Joyce, 1943- author (New York : FaithWords, 1995)
Worry, doubt, confusion, depression, anger, and feelings of condemnation: all these are attacks on the mind. If you suffer from negative thoughts, take heart! Joyce Meyer has helped millions win these all-important battles and she can help you too. The beloved author and minister shows you how to deal with thousands of thoughts you have every day and focus your mind to think the way God thinks. She shares the trials, tragedies, and ultimate victories from her own marriage, family, and ministry that led her to life-transforming truth